2006
DOI: 10.1007/s10334-006-0026-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Spatial Distribution of Magnetic Dipoles on Lamor Frequency Distribution and MR Signal Decay – a Numerical Approach Under Static Dephasing Conditions

Abstract: Cells loaded with superparamagnetic iron oxide (SPIO) cause relatively strong magnetic field distortions, implying that field position effects of neighboring SPIO loaded cells have to be accounted for. We treated SPIO loaded cells as magnetic dipoles in a homogeneous magnetic field and computed the 3D frequency distribution and the related signal decay using a numerical approach under static dephasing conditions. The volume fraction of dipoles was kept constant for all simulations. For larger randomly distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 34 publications
0
12
0
2
Order By: Relevance
“…Furthermore, as reported by Simon et al [16], free extracellular ferumoxtran-10 ultrasmall superparamagnetic iron oxide (USPIO) particles have shown a higher R 2 relaxivity as opposed to intracellular compartmentalized USPIO. These findings might be explained with regard to a recent paper [24], which demonstrated faster MR signal decay in case of uniformly distributed magnetic dipoles (e.g., SPIO in liquid solution) as compared to compartmentalized magnetic dipoles (e.g., SPIO ingested in cells).…”
Section: Discussionmentioning
confidence: 79%
“…Furthermore, as reported by Simon et al [16], free extracellular ferumoxtran-10 ultrasmall superparamagnetic iron oxide (USPIO) particles have shown a higher R 2 relaxivity as opposed to intracellular compartmentalized USPIO. These findings might be explained with regard to a recent paper [24], which demonstrated faster MR signal decay in case of uniformly distributed magnetic dipoles (e.g., SPIO in liquid solution) as compared to compartmentalized magnetic dipoles (e.g., SPIO ingested in cells).…”
Section: Discussionmentioning
confidence: 79%
“…Pintaske et al [19] showed that the spatial distribution of magnetic dipoles is an important factor that determines the resonance frequency distribution and hence the MR signal decay. They found the frequency distribution to be nonLorentzian, which led to non-monoexponential TEdependent signal decay.…”
Section: Signal Decaymentioning
confidence: 99%
“…In molecular imaging, injection of paramagnetic markers permits passive tracking [4,10], in the in vivo MR imaging of stem cells [11,12] and qualitative and quantitative assessment of holmium-loaded microspheres [13]. Superparamagnetic iron-oxide (SPIO) nanoparticles have recently been exploited as contrast agents for non-invasive cell tracking, quantification of tissue perfusion and target-specific imaging, and for the detection of gene expression [11,[14][15][16][17][18][19][20][21]. Magnetically labeled cells create intense magnetic field distortions within and around the cells, leading to enhanced signal dephasing in GE sequences.…”
Section: Introductionmentioning
confidence: 99%
“…Dieses wurde bereits vorgestellt und zum Studium verschiedener Effekte im Zusammenhang mit paramagnetischen Suszeptibilitätsverteilungen verwandt [14]. Auf die wichtigsten Sachverhalte soll im Folgenden eingegangen werden.…”
Section: Numerisches Modellunclassified
“…Dieses Dipolfeld ist identisch mit der Feldstörung außerhalb eines sphäri-schen Objektes mit Radius a (Abb. 3) [14]. (6) Dabei ist M die Magnetisierung des Objektes relativ zum umgebenden Medium.…”
Section: Abbildung 1 Elektronenmikroskopische Aufnahmen Menschlicher unclassified